Aorto-prosthetic-pulmonary fistula: Recurrent severe hemoptysis - Gastambide, Carmelo M.; Martinez Apezteguia, José L.; Ormaechea, Carlos; Berazategui, R.; Calleriza, F. (Cirugía del Uruguay, 1982)
The authors present a clinical case of a thoracic aorta prosthesis after resection of an aneurysm that underwent infection as a complication. The symptoms were; recurrent serious hemoptisis, 38 months after the initial surgery. The authors emphasize the low frequency of this entity; being as far as we know the first case in our country. The surgical approach used and the therapeutical possibilities of one or two succesive surgeries in further cases are discussed.